A Reparameterized Weighted Lindley Distribution: Properties, Estimation and Applications - Mota, Alex; Ramos, Pedro Luiz; Ferreira, Paulo; Tomazella, Vera; Louzada, Francisco (Revista Colombiana de Estadística, 2021)
In this paper, we discuss several mathematical properties and estimation methods for a reparameterized version of the weighted Lindley (RWL) distribution. The RWL distribution can be particularly useful for modeling reliability (survival) data with bathtub-shaped or increasing hazard rate function. The inferential procedure to obtain the parameter estimates is conducted via the maximum likelihood approach considering random right-censoring. Extensive numerical simulations are carried out to investigate and evaluate the performance of the proposed estimation method. Finally, the potentiality of the RWL model is analyzed by employing two real data sets.